Partially Erupted Prominence Material as a Diagnostic of Coronal Mass Ejection Trajectory - B. A. Hovis‐Afflerbach; B. J. Thompson; E. I. Mason (Space Weather)
Abstract Coronal mass ejections (CMEs) are energetic releases of large‐scale magnetic structures from the Sun. CMEs can have impacts on spacecraft and at Earth. This trajectory is typically assumed to be radial, but often the CME moves outward with some spatial offset from the source region where the eruption initially occurred. A CME is frequently accompanied by a prominence eruption, a movement of cool, dense material up into the corona that can be ejected or fall back down. We investigate eruptions in which some portion of the prominence material falls back to the Sun along field lines which have reconfigured in the eruption, rather than draining back to the source or escaping with the CME. Using a method called persistence mapping, 304 Å images from the Solar Dynamics Observatory (SDO), and coronagraph images from the Solar and Heliospheric Observatory, we measure and compare the offsets in latitude of 20 CMEs and their respective prominences with respect to the source region. The 20 events were chosen to sample over the first 10 years of the SDO mission. We find that the offsets are correlated. We find no difference between eruptions offset toward the equator or the poles, suggesting that the offset is a result of local changes in the eruptive field, rather than of the Sun's global magnetic field structure. These findings help us contextualize individual eruptions and highlight changes in the local magnetic field associated with the prominence eruption.